Causality Analysis of Volatility in Exchange Rate and Stock Market Prices: A Case Study of Pakistan - Khan, Rana Ejaz Ali; Ali, Rafaquat (Asian Economic and Financial Review, 2015)
This study attempted to investigate the direction of causation between the volatilities of exchange rate and stock market prices in Pakistan. Monthly time series data of Karachi Stock Exchange prices (KSE-100 Index) and exchange rate of Pakistan (Rupee against US Dollar) is used for the period of January 1992 to February 2013. Philips Perron (PP) unit root test is applied to check the stationarity. PP test results show that all variables were stationary at first difference. GARCH model is applied on each variable to measure the volatility. Then the series of each variable are used for Granger causality analysis. The results of Granger causality test show a bidirectional relationship between the exchange rate volatility and the variability of stock market prices in Pakistan.